Cervicothoracic Neurenteric Cyst With Contralateral Diaphragmatic Hernia: An Unusual Combination. (September 2021) - Worrell, Stephanie; Randall, Alice; O'Donnell, Brighid
We describe a premature male infant who died from complications resulting from two malformations: a large left-sided diaphragmatic hernia and a right-sided cervicothoracic neurenteric cyst. The findings of the first limited prenatal ultrasound led to the incorrect diagnosis of right-sided diaphragmatic hernia. Vertebral anomalies, commonly associated with neurenteric cysts, and an intrathoracic stomach, were not identified until autopsy examination. A literature review describes only one partly similar case relating a neurenteric cyst to the jejunum associated with an ipsilateral diaphragmatic defect identified on prenatal ultrasound. The second report of this combination raises the question of a developmental relationship.